Changes in the bioactivity of einkorn wheat during the maturation period and their effect on the properties of einkorn bread - Erkolencik, Mehmet Fatih; Kahraman, Burcu; Ozulku, Gorkem; Tulukcu, Eray; Goktas, Hamza; Sagdic, Osman; Arici, Muhammet (Tubitak Scientific & Technological Research Council Turkey, 2024)
Immature cereals may contain higher levels of nutrients than mature cereals. Immature and mature einkorn wheats were compared in terms of physicochemical, technological, rheological, and nutritional qualities and their performances for making bread were revealed. The values for thousand grain weight, hectoliter weight, sedimentation value and falling number of immature and mature einkorn wheat samples were 23.25-32.29 (g), 72.32-79.11 (kg/hL), 15.02-18.07 (mL) and 312-341 (sec), respectively (p <= 0.05). Immature einkorn wholegrain flour (IEWF) contains more than twofold mineral substance than mature einkorn wholegrain flour (MEWF). The total phenolic content and antioxidant properties of IEWF were found to be higher than those of MEWF. The empirical rheological properties of IEWF were higher than those of MEWF except for degree of softening . The G ' ' of both IEWF and MEWF were always found higher than the G '', '' , so they exhibited elastic behavior. The crust color brightness values of breads made from IEWF and MEWF were significantly different from bread made from commercial wheat wholegrain flour (CWF), but similar values were obtained for crumb color. The overall acceptability score of IEWF bread was similar to CWF bread, thus IEWF could be a good candidate for bread making or use in different food formulations.
Keywords: Immature and mature einkorn wheat flours; rheological properties; bioactive properties; bread baking; sensorial evaluation; ANTIOXIDANT; MONOCOCCUM; IMMATURE; QUALITY; Agriculture; Forestry